Progress on Poxvirus E3 Ubiquitin Ligases and Adaptor Proteins - Cui, Haoran; Zhang, Yaxian; Zhang, Leiliang (Frontiers in Immunology, 2021)
Poxviruses have evolved a variety of innate immunity evasion mechanisms, some of which involve poxvirus-encoded E3 ubiquitin ligases and adaptor proteins. Based on their functional domains and ubiquitin transfer mechanisms, these poxvirus-encoded E3 ubiquitin ligases and adaptor proteins can be divided into five categories: PRANC, ANK/BC, BBK, P28/RING, and MARCH proteins. Although the substrates of many poxvirus E3 ubiquitin ligases remain to be discovered, most of the identified substrates are components of the innate immune system. In this review, we discuss the current research progress on poxvirus-encoded E3 ubiquitin ligases and adaptor proteins to provide mechanistic insights into the interplay between these viruses and their hosts.